Litsa vlasti . Litsa vlasti . Faces of Power . Лица власти - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A lawyer Konstantin Lubenchenko tells about his experience of working in the Parliamentary Center of Russian Federation and discusses the possibility of the development of parliamentarism in Russia. Юрист Константином Лубенченко рассказывает о своем опыте работы в парламентском центре Российской Федерации и рассуждает о возможности построения парламентаризма в России.